Multicomponent self-assembly of a pentanuclear Ir–Zn heterometal–organic polyhedron for carbon dioxide fixation and sulfite sequestration. Issue 29 (2nd March 2016) - Li, Xuezhao; Wu, Jinguo; He, Cheng; Zhang, Rong; Duan, Chunying
Abstract : An iridium-containing pentanuclear metal–organic polyhedron was constructed via a subcomponent self-assembly. The three equatorial Zn(ii ) ions in the structure induced atmospheric carbon dioxide transformation as carbonate and sulfur dioxide as sulfite with bonding to the three metal centers. Abstract : By incorporating a fac -tris(4-(2-pyridinyl)phenylamine)iridium as the backbone of the tripodal ligand to constrain the coordination geometry of Zn(ii ) ions, a pentanuclear Ir–Zn heterometal–organic luminescent polyhedron was obtained via a subcomponent self-assembly for carbon dioxide fixation and sulfite sequestration.